Analisis Kepuasan Mahasiswa terhadap Penggunaan Aplikasi DANA Menggunakan Metode SWOT - Yuliana Yuliana; Siti Nurwanti; Betanika Nila Nirbita (UNHI Press, 2023)
The aim of the study was to find out how satisfied Economics Education students class of 2020 were with the DANA application, which can be used as a medium for transactions in students' daily lives. DANA is intended to make it easier for students to make transactions that support their daily needs wherever they are and whenever they need it. However, there are some drawbacks in using the DANA application. One is that a reliable internet connection is required. This type of research uses quantitative analysis and a SWOT approach for DANA applications. Based on the findings of this research analysis, the researchers advise DANA developers to make regulations related to the development of DANA applications from the start in order to minimize unwanted risks as early as possible, handle them properly, and prevent losses to DANA parties and users. In addition, it is hoped that students will gain a better understanding and expertise of the DANA application to be able to use it properly. 75.8% of respondents to a survey conducted by researchers agreed that DANA can be applied in everyday life. And 68.9% of users are satisfied with the performance of the DANA application. These findings indicate that the DANA application is prepared for comparison among college students.